2013
DOI: 10.5194/acp-13-599-2013
|View full text |Cite
|
Sign up to set email alerts
|

Extreme <sup>13</sup>C depletion of CCl<sub>2</sub>F<sub>2</sub> in firn air samples from NEEM, Greenland

Abstract: Abstract.A series of 12 high volume air samples collected from the S2 firn core during the North Greenland Eemian Ice Drilling (NEEM) 2009 campaign have been measured for mixing ratio and stable carbon isotope composition of the chlorofluorocarbon CFC-12 (CCl 2 F 2 ). While the mixing ratio measurements compare favorably to other firn air studies, the isotope results show extreme 13 C depletion at the deepest measurable depth (65 m), to values lower than δ 13 C = −80 ‰ vs. VPDB (the international stable carbon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…To measure m/z 33 of OCS without interferences, further improvement of peak separation of OCS with interferences is required by changing the parameter of the separation in the system and/or data processing. For example, a custom-made MATLAB routine, which can extrapolate the peak tail of interference via an exponentially decaying function to distinguish the two gaseous species as described in Zuiderweg et al (2013), would enable us to analyse m/z 33 in addition to the standard ISODAT software used for isotope ratio measurements.…”
Section: Sulfur Isotope Ratio For Atmospheric Ocsmentioning
confidence: 99%
See 1 more Smart Citation
“…To measure m/z 33 of OCS without interferences, further improvement of peak separation of OCS with interferences is required by changing the parameter of the separation in the system and/or data processing. For example, a custom-made MATLAB routine, which can extrapolate the peak tail of interference via an exponentially decaying function to distinguish the two gaseous species as described in Zuiderweg et al (2013), would enable us to analyse m/z 33 in addition to the standard ISODAT software used for isotope ratio measurements.…”
Section: Sulfur Isotope Ratio For Atmospheric Ocsmentioning
confidence: 99%
“…Rather, δ 34 S(OCS) values of (10.5 ± 0.4) ‰ at the Suzukakedai campus might be more affected by anthropogenic OCS emission and/or less affected by oceanic OCS emissions compared to the samples collected in Israel or the Canary Islands with higher δ 34 S(OCS) values. Potential anthropogenic OCS sources are Chinese emissions from rayon production (rayon yarn and staple rayon) and coal (industry and residential emissions), as pointed out by recent OCS source inventories (Zumkehr et al, 2018). In fact, the OCS concentration in the vicinity of China is high based on satellite observation (Glatthor et al, 2015).…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
“…The US hole was sampled to a depth of 75.6 m; the EU hole was sampled to a depth of 77.8 m. More details on sampling procedure and other measurements on air from these two boreholes can be found in Buizert et al (2012). Further firn air sampling took place during July 2009 from a borehole located ∼ 250 m away from the 2008 boreholes (Zuiderweg et al, 2013). This borehole was sampled to a depth of 76.0 m with a firn air device from CSIRO and is referred to as "2009 hole".…”
Section: Firn Air Samplingmentioning
confidence: 99%
“…Isotope studies of CFCs and HCFCs in atmospheric samples have focused to date on source apportionment in the atmosphere using stable carbon isotope analysis. One study also applied stable chlorine isotope analysis (δ 37 Cl) and showed the potential for large enrichment factors due to photolysis in the stratosphere . In soils and waters CFCs are relatively stable compounds but may degrade due to biotic and abiotic processes such as microbial dechlorination , and reaction with zerovalent iron (ZVI). , Isotope analysis of CFCs in water, however, has only been reported once in a laboratory study demonstrating the viability of δ 13 C analysis of headspace for laboratory samples produced via abiotic degradation experiments with ZVI and for air samples collected near landfills .…”
mentioning
confidence: 99%